Pengembangan Inovasi Bolu Sakinah untuk Meningkatkan Pemasaran pada Media Online di Kabupaten Magetan - Linda Ayu Renggani; Maylinda Dwi Astuti; Hesti Dwi Wijayanti; Alifah Aprilia Ananda; Puji Nurhayati (Yayasan Literasi Sains Indonesia, 2024)
Today's people's lives cannot be separated from the activities of Micro, Small and Medium Enterprises (MSMEs). MSME activity is a form of business that plays an important role in the development and growth of the economy in Indonesia. Technological developments and increasing business competition make micro, small and medium enterprises (MSMEs) must have good initial marketing to be able to compete with other competitors. Utilizing internet marketing technological innovations in the form of digital marketing or internet marketing is a paradigm that needs to be understood, especially in today's business world. The purpose of this research is to provide innovation for the community in building a more modern business for MSME businesses, especially Sakinah cakes as an increase in sales turnover. The implementation method is carried out using several stages, namely 1) problem identification, 2) output and 3) conducting training and developing new innovations. The result of this activity is the product innovation of Sakinah cake which has packaging and branding. This activity is expected to make MSMEs develop and improve their marketing methods using digital marketing.